EKSISTENSI PENGADILAN TINDAK PIDANA KORUPSI DI INDONESIA DALAM PENEGAKAN HUKUM TINDAK PIDANA KORUPSI DI INDONESIA - Muhammad Afif (Ensiklopedia of Journal, 2018)
Corruption according to law is the behavior of public officials, both politicians or politicians and civil servants, who improperly and illegally enrich themselves or enrich those who are close to them, by misusing the public authority entrusted to them. According to the law of corruption eradication which is one of the most important agendas in improving governance in Indonesia. The Corruption Court is a court specifically dealing with Corruption cases. The Corruption Court is tasked and authorized to examine and decide on the Corruption Crime case whose prosecution was filed by the Corruption Eradication Commission.